2016
DOI: 10.1007/s00228-016-2157-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UGT1A9 genetic polymorphisms on monohydroxylated derivative of oxcarbazepine concentrations and oxcarbazepine monotherapeutic efficacy in Chinese patients with epilepsy

Abstract: In our study, we have demonstrated the effects of UGT1A9 genetic polymorphisms on MHD plasma concentrations and OXC therapeutic efficacy. Through MHD monitoring, we can predict OXC therapeutic efficacy, which may be useful for the personalization of OXC therapy in epileptic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…The elimination of OXC and MHD is mainly by binding with UGT enzyme to form glucuronic acid conjugate, which is then excreted in the urine. In our study, of the four SNPs (UGT1A4 rs2011425, UGT1A6 rs6759892, UGT1A9 rs2741049 and UGT2B15 rs1902023), we found UGT1A4 rs2011425 and UGT2B15 rs1902023 were signi cantly associated with MHD plasma concentretion, which was inconsistent with Lu et al's study [13], as MHD plasma concentration of UGT1A9 rs2741049 mutant allele T carriers was signi cantly lower than those non-carriers. It may be explained by differences in the age of the population, because Lu et al included both children and adults in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…The elimination of OXC and MHD is mainly by binding with UGT enzyme to form glucuronic acid conjugate, which is then excreted in the urine. In our study, of the four SNPs (UGT1A4 rs2011425, UGT1A6 rs6759892, UGT1A9 rs2741049 and UGT2B15 rs1902023), we found UGT1A4 rs2011425 and UGT2B15 rs1902023 were signi cantly associated with MHD plasma concentretion, which was inconsistent with Lu et al's study [13], as MHD plasma concentration of UGT1A9 rs2741049 mutant allele T carriers was signi cantly lower than those non-carriers. It may be explained by differences in the age of the population, because Lu et al included both children and adults in their study.…”
Section: Discussioncontrasting
confidence: 99%
“…UGT enzymes are a superfamily of key proteins that catalyze the glucuronidation of a wide range of AEDs, including Lamotrigine (LTG), CBZ and OXC [15,30,31]. A recent study have revealed that carriers of the UGT1A9 variant allele I399 C > T had significantly lower MHD plasma concentrations and poorer seizure control than noncarriers [16]. As for UGT2B7 rs7439366, the polymorphism causes a histidine-to-tyrosine substitution at position 268 of the protein, whose allele frequency in the Chinese population is 32.8% [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of OXC administered is excreted by the kidneys as the inactive glucuronide conjugates of the MHD by weakly inducible microsomal UDP-glucuronosyltransferases (UGTs), OXC, and unchanged MHD [15]. Studies have shown that UGT2B7 rs7439366 and UGT1A9 rs2741049 genetic polymorphisms probably contribute to the variability of enzymatic activity among individuals, resulting in different OXC plasma concentration and treatment response [13,16]. However, comprehensive studies are required to confirm the findings, and the data regarding the effects on OXC responsiveness was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney transplant patients homozygous for the UGT1A8*2 rs1042597 CC genotype had increased diarrhea occurrences when administrated the immune suppressants mycophenolate mofetil and cyclosporine compared to patients with the heterozygous and wild-type genotypes [87]. Patients with epilepsy who had the intronic UGT1A8 rs2741049 TT genotype had a lower response to oxcarbazepine than patients with the CC genotype [88].…”
Section: The Clinical Impact Of Ugt1a Genotype On Drug Response and Toxicitymentioning
confidence: 98%